Cost-Effectiveness Studies in the ICU: A Systematic Review*. Issue 8 (August 2019) - Wilcox, M. Elizabeth; Vaughan, Kelsey; Chong, Christopher A. K. Y.; Neumann, Peter J.; Bell, Chaim M.
Abstract : Objectives: Cost-effectiveness analyses are increasingly used to aid decisions about resource allocation in healthcare; this practice is slow to translate into critical care. We sought to identify and summarize original cost-effectiveness studies presenting cost per quality-adjusted life year, incremental cost-effectiveness ratios, or cost per life-year ratios for treatments used in ICUs. Design: We conducted a systematic search of the English-language literature for cost-effectiveness analyses published from 1993 to 2018 in critical care. Study quality was assessed using the Drummond checklist. Setting: Critical care units. Patients or Subjects: Critical care patients. Interventions: Identified studies with cost-effectiveness analyses. Measurements and Main Results: We identified 97 studies published through 2018 with 156 cost-effectiveness ratios. Reported incremental cost-effectiveness ratios ranged from –$119, 635 (hypothetical cohort of patients requiring either intermittent or continuous renal replacement therapy) to $876, 539 (data from an acute renal failure study in which continuous renal replacement therapy was the most expensive therapy). Many studies reported favorable cost-effectiveness profiles (i.e., below $50, 000 per life year or quality-adjusted life year). However, several therapies have since been proven harmful. Over 2 decades, relatively few cost-effectiveness studies in critical care have been published (average 4.6 studies per year). There has been a more recent trend toward using hypothetical cohorts and modeling scenarios without proven clinical data (2014–2018: 19/33 [58%]). Conclusions: Despite critical care being a significant healthcare cost burden there remains a paucity of studies in the literature evaluating its cost effectiveness. Abstract : Supplemental Digital Content is available in the text.